The accumulation of metal (Co, Cr, Cu, Mn and Zn) in freshwater Ulva (Chlorophyta) and its habitat - Rybak, Andrzej; Messyasz, Beata; Łęska, Bogusława (Springer, 2013)
The possibility of using freshwater Ulva (Chlorophyta) as a bioaccumulator of metals (Co, Cr, Cu, Mn and Zn) in lake and river water was examined weekly in the summer of 2010 in three types of samples: the water, the sediment and the thalli of Ulva. Samples of freshwater Ulva were collected from two aqueous ecosystems lie 250 km away from the basin of the Baltic Sea and 53 km from each other. A flow lake located in the centre of the big city was the first water reservoir (10 sites) and second, the suburban river (6 sites). The mean metal concentrations in the Ulva tissue from the river and the lake decreased in the following order: Mn>Zn>Cr>Cu>Co and Mn>Cr>Zn> Cu>Co, respectively. Moreover, a negative and statistically significant correlation between Mn concentrations in the Ulva thalli and the river water was observed. Additionally, numerous correlations were noted between the different concentrations of metals within the Ulva thalli, in the water and in the sediment. The great concentrations of Mn and Zn and the smallest of Co were found in thalli of Ulva, irrespective of the type of the ecosystem from which samples of algal thalli originated. Freshwater Ulva populations examined in this study were clearly characterized a dozen or so times by the higher Mn and Cr accumulation than taxa from that genera coming from sea ecosystems. The calculated bioconcentration factor (BCF) confirm the high potential for freshwater Ulva to be a bioaccumulator of trace metals in freshwater ecosystems.
Keywords: Chlorophyta; bioconcentration factor; bioaccumulator; freshwater Ulva; heavy metals